ANALISIS PROBLEMATIKA PENGAJARAN BAHASA ARAB DI PERGURUAN TINGGI ISLAM - Barowi Barowi (Intelegensia : Jurnal Pendidikan Islam, 2014)
AbstractStudents of Islamic University who graduated from public schools and madrasah or pesantren comes from an imbalance in the understanding of the Arabic language. For those who come from graduates of the schools or madrassas better understand the Arabic language than those who had graduated from public schools. This creates difficulties / problems for lecturers in teaching Arabic in the classroom. Departing from the above case the necessary solutions to overcome them. Among others are; a) designing a specific curriculum for graduate students from public schools, b) grouping students by ability or special training for graduate students from public schools, and c) increase the interest and motivation of students' public school graduates. In addition, it is also necessary to improve the quality of lecturers through workshop, training or orientation regarding methods of learning Arabic, study visits to universities and other Muslim and the need for lecturers Arabic continuing education to a higher level of at least a master, thank reaches S3 ( doctorate).Keywords: Arabic, problematic, student, education